Respuesta :

Answer:

[tex]\displaystyle r=\frac{3t}{t-1}[/tex]

Step-by-step explanation:

We are given the formula:

[tex]\displaystyle t=\frac{r}{r-3}[/tex]

And we are asked to make r the subject of the formula.

We can multiply both sides by r - 3. This reduces the denominator on the right-hand side:  

[tex]t(r-3)=r[/tex]

Distribute:

[tex]rt-3t=r[/tex]

Subtracting rt from both sides yields:

[tex]-3t=r-rt[/tex]

Factoring:

[tex]-3t=r(1-t)[/tex]

Divide and simplify:

[tex]\displaystyle \begin{aligned} r & = \frac{-3t}{1-t} \\ \\ & = \frac{3t}{t-1}\end{aligned}[/tex]

In conclusion:

[tex]\displaystyle r=\frac{3t}{t-1}[/tex]